El Mercado Común del Cono Sur en la integración latinoamericana - Rosas, María Cristina (Revista Mexicana de Política Exterior, 2022)
The author introduces a finished study of the background, formation, objectives, operation and components of the South Cone Common Market (commonly known as the Mercosur). Among other goals, this body aspires to the creation of a South American Free Trade Area (ALCSA, by its initials in Spanish). She explains why the Mercosur is a unique experience in the history of regionalizing processes in Latin America. Stating that from the beginning, it was conceived of as a political project to end the crisis and improve participation by the Rio de la Plata Basin countries in international affairs. She also mentions and explains core articles and chapters of the Asunción Agreement, the document that lays the basis for and directs the Mercosur, points out the benefits the member countries have enjoyed from this strategic alliance, and sets out some important differences between the Mercosur and the Free Trade Area of the Americas (ALCA) project.